ПОВЫШЕНИЕ ТОЧНОСТИ РЕГУЛИРОВАНИЯ НАПРЯЖЕНИЯ НА ЕМКОСТНЫХ НАКОПИТЕЛЯХ ЭНЕРГИИ СИСТЕМ ИМПУЛЬСНОЙ ПЛАЗМОЭРОЗИОННОЙ ОБРАБОТКИ ГЕТЕРОГЕННЫХ ТОКОПРОВОДЯЩИХ СРЕД - Захарченко, С.Н.; Руденко, Ю.В.; Черкасский, А.П. (Інститут електродинаміки НАН України, Київ, 2016)
The methods for improving the accuracy of voltage regulation in capacitive energy storage devices and variants of their technical implementation were analyzed. With the use of the proposed models of charging device units of discharge pulse generator for plasma-erosion treatment of heterogeneous conductive media a transients in them were calculated. For the ideal charging LC-circuit the dependency of the of voltage regulation imprecision value in capacitive energy storage device from its characteristic impedance and correlation between the initial conditions on its parts was determined. The algorithms for adjusting the charging current threshold value were developed. Suggested algorithms provide highly accurate voltage regulation in capacitive energy storage devices while those devices are charged with a high speed. It is shown that the use of working mode of capacitive energy storage devices for which charge pulse repetition rate is much higher than discharge pulse repetition rate allows to reduce the voltage control imprecision value for such devices to ±(1÷3)% or less. References 21, figures 6.